Implementation of Vocational Life Skills Program to Strengthen Skills Education - Mufidah, Diroyatul; Hanif, Muh. (Thawalib: Jurnal Kependidikan Islam, 2025)
The Vocational Life Skills Program is an educational breakthrough designed to equip students with applied skills, respond to globalization, and strengthen skill-based education in the madrasah environment. This study aims to analyze the implementation of the vocational life skills program to enhance skills education at State Islamic Senior High School 2 Banyumas. The researcher used a descriptive qualitative method with a case study design. Data were collected through observation, interviews, and documentation, and then analyzed interactively through data reduction, presentation, and conclusion drawing. The results show that the Life Skills Program is intrakurricular and dialectical, allowing students to choose majors based on their interests. Learning comprises 70% practical experience through industrial visits, a 160-hour internship, and 30% theory. It involves eight majors emphasizing Islamic values, independence, and job readiness. This program develops technical and soft skills, fosters professional ethics, teamwork, and communication, preparing graduates to be highly competitive and accomplished. Challenges include a complex curriculum, limited time, inadequate facilities, and teacher competency. Solutions involve project-based learning, industry collaboration, digital simulations, and continuous teacher training to keep the program relevant and practical. Conclusion: Strengthening the vocational life skills program is a strategic effort to equip students with practical skills, develop holistic character, and respond effectively to the challenges of 21st-century life.